Indian Soldiers in World War I Race and Representation in an Imperial War - Jarboe, Andrew Tait (Book collections on Project MUSE., 2021)
""Indian Soldiers in World War I" follows the experiences of Indian soldiers deployed to European battlefields during World War I and examines the imperial and military policies that shaped their involvement on the Western Front"--